FAKTOR PENGHAMBAT DALAM PEMASARAN JASA PENDIDIKAN ISLAM - Khabib Sharifudin (CV. ADIBA AISHA AMIRA, 2025)
The paradigm of education has changed. Previously, education was seen and studied from a social point of view, but now society sees education more from a corporate point of view. Islamic educational institutions have to make strategies, especially to promote their programmes. This article uses a literature approach, where relevant literature is taken based on the topic of discussion. It will discuss various approaches proposed by experts, including distintive capabilities, profit capabilities, focus, communication, and innovation. These strategies must be implemented to ensure the sustainability of Islamic education institutions. However, the cornerstone that Islamic education marketing strategies must be is in accordance with Islamic principles and ethics, helping the cause of good education, and ensuring quality, honesty, and integrity. No matter how difficult it is to implement, there is a strategy. The things that hinder the marketing of these educational services are more temporary and stem from factors such as intense competition among existing schools, bureaucracy and frequently changing regulations, and lack of innovation from management. Undoubtedly, this situation should be prevented by using various methods that can show indications of increasing student interest, such as making clear and consistent regulations, improving the quality of education, and consistent evaluation. The existence of these preventive strategies and solutions will make Islamic education institutions better equipped to promote their educational programmes.